Knowledge on utilization of moringa as a nutrient supplement among people of Gadam community, Kwami local government area of Gombe state, Nigeria - Japhet Y. Galaboyi,; Lukson Lugard,; Dauda Rifkatu Samaila,; Pauline J S Doka,; Henrietta A. Okedo, (International Journal For Research In Health Sciences And Nursing, 2024)
Background: Utilization of natural product of plant origin having fewer side effects has gain popularity over the years. There is immense scope from natural product that can intimate health nutritious benefit rather than traditional benefit. However, the emphasis of this call appears more on the utilization of locally available and indigenous natural product to combat health. The study seeks to assess the knowledge and utilization of moringa as nutrient supplement among people of Gadam community. Method: A descriptive survey research designed was adopted for the study, the study targeted all resident of Gadam community who are 30 years and above using a sample size of 110; data was collected via structured interview questionnaires, which was analyzed using SPSS V24 and results presented in frequency and percentage tables. Results: Majority 41.3% of the respondents fall into the age group of 30 – 35 years, while few of the respondents fall into the age group of 45-49years accounting for 10.1% of the surveyed. 99.1% of the respondent knows that moringa is a tree plant, 0.9% doesn’t know moringa as a tree plant, 98.2% of the respondent have knowledge on nutritional value of moringa, 1.8% of the respondent are not knowledgeable on its nutritional value, 99.1% of the respondent are also aware that moringa has a medicinal benefits 0.9% are not aware of its medicinal benefits. 54.13% of the respondents strongly agreed that dried moringa leaves can be used as spices, 43.12% agreed while 0.92% strongly disagree also, 1.84% disagree, factors influencing utilization of moringa include taste of moringa as 53.21% of the respondent strongly agreed, 23.85% of the respondents agreed, 47.71% of the respondent strongly agreed that low sensitization on moringa affect its utilization as a tree plant, 32.86% agreed also. Conclusion: The results concluded that the respondents had a good knowledge on moringa, the extent to which moringa is utilized as a food supplement in Gadam community is good, low sensitization and taste of moringa are key factors identified to affect moringa utilization. The researcher therefore recommends that the health care providers should deliver quality health talk and emphases on the nutritional content of moringa.